Analysis of The Role of Banking in Supporting Decarbonization Policy in The Shipping Sector in Indonesia - Zulfakhri, Ahlan (Universitas Pahlawan Tuanku Tambusai, 2025)
This study comprehensively analyzes banking policies and instruments in supporting the decarbonization of Indonesia's shipping sector, focusing on identifying challenges, opportunities, and strategic recommendations. A literature review shows that major banks in Indonesia, such as Bank Mandiri, BNI, and BRI, have taken strategic steps through the development of a comprehensive sustainable finance framework, although the maritime industry still faces challenges such as high loan interest costs and a lack of public financing support. With consistent support and commitment from banks, Indonesia is expected to make optimal use of its maritime potential while preserving the environment and encouraging sustainable economic growth. This research aims to provide a conceptual and practical framework for stakeholders in efforts to decarbonize Indonesia's shipping sector.